Morphometric parameters as risk factors for anterior cruciate ligament injuries – A MRI case-control study - Stijak, Lazar; Bumbaširević, Marko; Kadija, Marko; Stanković, Gordana; Herzog, Richard; Filipović, Branislav (Vojnosanitetski pregled, 2014)
Background/Aim. The anterior cruciate ligament (ACL) is the most frequently injured ligament of the knee, representing 50% of all knee injuries. The aim of this study was to determine the differences in the morphometry of knee injury patients with an intact and a ruptured anterior cruciate ligament. Methods. The study included 33 matched pairs of patients divided into two groups: the study group with the diagnosis of anterior cruciate ligament rupture, and the control group with the diagnosis of patellofemoral pain but no anterior cruciate ligament lesion. The patients were matched on the basis of 4 attributes: age, sex, type of lesion (whether it was profession-related), and whether the lesion was left- or right-sided. Measurements were carried out using magnetic resonance imaging (MRI). Results. The anterior and posterior edges of the anterior cruciate ligament in the control group were highly significantly smaller (p < 0.01; in both cases). The control group showed a statistically significantly larger width of the anterior cruciate ligament (p < 0.05). A significant correlation between the width of the anterior cruciate ligament and the width (p < 0.01) and height (p < 0.05) of the intercondylar notch was found to exist in the control group, but not in the study group (p > 0.05). The patients in the control group showed a shorter but wider anterior cruciate ligament in comparison to their matched pairs. The control group of patients was also characterized by the correlation between the width of the intercondylar notch and the width of the anterior cruciate ligament, which was not the case in the study group. Conclusions. According to the results of our study we can say that a narrow intercondylar notch contains a proportionally thin anterior cruciate ligament, but we cannot say that this factor necessarily leads to rupture of the anterior cruciate ligament.